The Effect of Citronella Oil Concentration (Cymbopogon nardus (L. ) Rendle) on the Quality of Shampoo and Antifungal Activity of Candida albicans - Lidya Ameliana; Alik Almawadah; Lestyo Wulandari (Universitas Padjadjaran (Unpad), 2019)
Citronella oil (Cymbopogon nardus (L.) Rendle) was formulated into shampoo preparations to overcome dandruff. Dandruff is a condition which exfoliation of the excess horny layer on the scalp and forms fine scales caused by fungal infections of Candida albicans. The purpose of this study was to determine the antifungal activity and quality of the citronella oil shampoo. Citronella oil was taken using a steam distillation method. The oil produced has good quality because it meet the range of organoleptic requirements, which were the refractive index 1.483, density 0.890g/mL and citronellal content 41.720%. MIC (Minimum Inhibition Concentration) to find out the lowest concentration of shampoo which can still inhibit the growth of Candida albicans was 2%. Citronella oil then formulated into shampoo with F1 (4%) F2 (6%) and F3 (8%) oil concentrations. The results of the quality of shampoo evaluation showed that all formulations met the requirements of pH, viscosity, and foam height. In testing the antifungal activity of shampoo was known that the greater the concentration of oil in the shampoo, the greater the antifungal activity in the shampoo.Keywords: Citronella oil, shampoo, antifungal activity